Evaluation of Some Inflammatory and Biochemical Markers in Obese and Lean Iraqi Women - Al-Jumaili, Farah T O (Al-Nahrain Journal of Science, 2018)
The present study aims to detecting several biochemical markers and cytokines in obese and normal lean Iraqi women. Forty women (20 obese and 20 lean) were chosen from different areas in Baghdad city there ages ranges between 20-37 years and body mass index (BMI) between20.75-35.6 Kg/m². The study showed a high significant increment in Fasting Blood Glucose (FBG), serum cholesterol and Homeostasis Model Assessment (HOMA) in obese women as compared with lean and a significant increment in HDL (High Density Lipoprotein) in lean women when compared with obese ones. A significant correlation coefficient (r) was noticed between BMI and studied parameters, FBG, cholesterol, triglyceride, insulin, HOMA, high sensitive C Reactive Protein (hs-CRP), Tumor Necrosis Factor alfa (TNF-α) and IL-6.